2011
DOI: 10.4236/ijg.2011.22014
|View full text |Cite
|
Sign up to set email alerts
|

New Constraints from Pb-Evaporation Zircon Ages of the Méiganga Amphibole-Biotite Gneiss, Central Cameroon, on Proterozoic Crustal Evolution

Abstract: The amphibole biotite gneiss (ABGn) in the Méiganga area forms part of a meta volcano-sedimentary sequence of the Adamawa Yade domain (AYD), Central African Fold Belt (CAFB). This sequence shows affinity with immature sediments (greywackes, arkoses) with intercalation of mafic lavas or tuffs. New 207 Pb/ 206 Pb zircon evaporation ages for two ABGn samples range from 1887 -2339 Ma and from 675 -889 Ma, respectively. These ages and evidence from internal zircon structures indicate that igneous rocks of Archean t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This magmatism which is materialized in the outcrops by volcano-sedimentary formations associated with meta-mafic and felsic volcanic and plutonic rocks, orthogneisses and dolerite dykes show continental tholeiite and alkaline signature (Souza & Moura 1995;Vicat et al, 2001;Neves, 2003;Guimarães et al, 2012;Viana & Battilani 2014). In the Central Cameroon Domain in Central African Orogenic Belt (Figure 2(a) and Figure 2(b)), the tonian ages are mentioned in the biotite-muscovite granitoids (~926 Ma) and amphibole-biotite gneiss (~889 Ma) respectively in the Ngaoundere cliff and Meiganga area (Tchameni et al, 2006;Ganwa et al, 2011). But these ages have been interpreted as inherited and of no geological significance, probably due to the lack of more detailed studies.…”
Section: General Geological Contextmentioning
confidence: 99%
“…This magmatism which is materialized in the outcrops by volcano-sedimentary formations associated with meta-mafic and felsic volcanic and plutonic rocks, orthogneisses and dolerite dykes show continental tholeiite and alkaline signature (Souza & Moura 1995;Vicat et al, 2001;Neves, 2003;Guimarães et al, 2012;Viana & Battilani 2014). In the Central Cameroon Domain in Central African Orogenic Belt (Figure 2(a) and Figure 2(b)), the tonian ages are mentioned in the biotite-muscovite granitoids (~926 Ma) and amphibole-biotite gneiss (~889 Ma) respectively in the Ngaoundere cliff and Meiganga area (Tchameni et al, 2006;Ganwa et al, 2011). But these ages have been interpreted as inherited and of no geological significance, probably due to the lack of more detailed studies.…”
Section: General Geological Contextmentioning
confidence: 99%
“…Several works have been made in the Méiganga area and its surroundings for the geological knowledge of the area [5,[9][10][11][12][13]. These studies revealed that the geological formations of the Méiganga area and its environs are part of the central Panafrican belt of Cameroon, which is denominated has the Adamawa Yadé domain (AYD) ( Figure 2).…”
Section: Geological and Tectonical Settingmentioning
confidence: 99%
“…It is underlain by syntectonic, late-tectonic, and posttectonic granitoids [9,10] which intrude in older metamorphic rocks. The granitoids present in the study area include biotite-muscovite granite and pyroxene amphibole-biotite granite [12,13]. The metamorphic host rocks consist of 2.1Ga metasediments (metamorphized conglomerates and clay sandstones) and orthogneisses, which were reworked during the Panafrican orogeny [11].…”
Section: Geological and Tectonical Settingmentioning
confidence: 99%